2020
DOI: 10.3390/ijerph17186905
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Time Perspective of Blue-Collar Workers at the Shipyard

Abstract: Background: The aim of the research was to investigate the association between time perspective in relation to burnout and successful ageing of blue-collar workers with physically highly demanding work and low autonomy. Shipyard blue-collar workers usually do predominantly manual labor versus white-collar workers, whose jobs do not usually involve physical work. Methods: 497 participants workers in a shipyard in the north of Spain. Ages were between 20 and 69 (M = 46.62, SD = 10.79). We used the Zimbardo Time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Another study by Meidani et al (2019) observed correlational associations of the individual TP dimensions to the burnout phenomenon among a sample of teachers. Similar results were reported by Detaille et al (2020) for blue-collar workers in the naval sector. Two other studies, one with a sample of a variety of blue-collar workers from Spain (Reig-Botella et al, 2021) and another with a sample of industrial workers versus MBA-students (Papastamatelou & Unger, 2018) were able to show that differences in burnout proneness across several branches and professions depend on differing TPs in these branches and professions.…”
Section: Introductionsupporting
confidence: 89%
“…Another study by Meidani et al (2019) observed correlational associations of the individual TP dimensions to the burnout phenomenon among a sample of teachers. Similar results were reported by Detaille et al (2020) for blue-collar workers in the naval sector. Two other studies, one with a sample of a variety of blue-collar workers from Spain (Reig-Botella et al, 2021) and another with a sample of industrial workers versus MBA-students (Papastamatelou & Unger, 2018) were able to show that differences in burnout proneness across several branches and professions depend on differing TPs in these branches and professions.…”
Section: Introductionsupporting
confidence: 89%
“…Despite the aforementioned limitations, our study provides evidence that JDC in its simplistic form continues to forefront occupational well-being. Thus, with a methodologically different approach (LPA) and with a sample with a wide range of occupations, typically characterized by stressful occupations [12][13][14][15][16][17][18][19][20][21], our study highlights that redesign jobs through the two main job characteristics have impact on employees' burnout and engagement. The most salient aspect of the current study is that organizations should invest in workers' control.…”
Section: Practical Implicationsmentioning
confidence: 94%
“…Our study adds on previous studies, a sample with a very large number of employees (i.e., 6357) from different activity sectors and occupations (health, bank, retail, and contact center). This sample variety is important not only because we expected that the results provide conclusions possible of generalization of main assumptions of JDC to a wide range of occupational sectors, but also, because these occupations are in unique work environments largely acknowledgeable as stressful [12][13][14][15][16][17][18][19][20][21]. It is in this stressful work environment that the job control may present more expression in mitigating the job demands effect, that is, that buffer hypothesis may occur [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a gap between notions of aspiration and prospects of achievement among younger and older staff, with younger staff being more content with just having succeeded in getting a job rather than being satisfied with the work they are doing. As working conditions within the shipyard are harsh [43], once they spend longer in the organization, they become less satisfied with their job and their contentment with aspects of their work is reduced.…”
Section: Theoretical Backgroundmentioning
confidence: 99%